The Implementation of Migration Theology according to Gemma Tulud Cruz in the Talithakum Network of Yogyakarta - Leo Agung Tyas Prasaja; Gregorius Sigit Triwahyudi; Andreas Agung Yubile; Fermino Billy Deva Septaldo (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Talithakum is an internationally networked organization that works on humanitarian issues, especially human trafficking. It is managed collaboratively by leaders of women's religious congregations worldwide. In Indonesia, Talithakum is managed by IBSI or Ikatan Biarawati Seluruh Indonesia (Nuns Association of Indonesia) and is spread into nine networks. One of these networks is the Talithakum Yogyakarta Network. Using the literature study method, this research explores and examines the values of Gemma Tulud Cruz's theology of migration in the Talithakum Yogyakarta Network. The results showed that Talithakum Yogyakarta Network, as a humanitarian organization, applies the values of Gemma Tulud Cruz's theology of migration. The spirit of solidarity, the spirituality of courageous hope, and the crucified people live clearly in various work programs run by Talithakum Yogyakarta Network. The values of Cruz's theology of migration are seen from simple efforts such as educational movements as a preventive stage to assistance and sustainable handling actions for migrants. Talithakum Network Yogyakarta is committed to realizing a world free of human trafficking. This commitment is also important to be owned by various elements of society, including the Church, to build civilization and a dignified life.